Division of Lanao Del Sur 1, DepEd-ARMM: Its Vital Role in Peacebuilding and Reconciliation in the Post-Conflict Settings - Sumagayan, Sahanee (JPAIR Multidisciplinary Research, 2018)
The Philippines has experienced over 40 years of internal armed conflict in the Southern Island of Mindanao, as the resident Muslim population continues to demand self-determination. Hence, this study aimed to locate and explore frameworks on building peace initiatives and conflict tools resolution as the symbolic rites of procedures. Specifically, it sought to: 1) Understand the meaning of peacebuilding and reconciliation in the context of post-conflict settings; 2) Define extremism; 3) Determine the role of Division of Lanao del Sur 1, DepEd-ARMM in preventing extremism, and 4) Determine how education can counter religious extremism. Using documentary analysis method, data were obtained and collected from the Mindanao State University (MSU) System library, the Armed Forces of the Philippines, the Philippine National Police, the Department of Education (DepEd-ARMM), the Department of Social Welfare and Development (DSWD), the Philippine National Red Cross (PNRC), and Bangon Marawi Task Force. There were six (6) key informants interviewed by the researcher. Based on the nature of the study, no statistical treatment of data gathered was done. This is the limitation of the study. Findings revealed that peacebuilding facilitates the establishment of durable peace and prevents the recurrence of violence through reconciliation, education, institutional and political building for economic transformation. The Division of Lanao del Sur 1, DepED-ARMM recommends that the government should create an independent commission to highlight measurable progress and determine the benchmarks that these programs have met.